CRYSTALLOGRAPHIC INSIGHTS INTO THE BIS[1-METHOXY-2,2,2-TRIS-(PYRAZOL-1-YLΚN2) ETHANE]-COBALT (II) BIS-PERCHLORATE COMPLEX - Davis, Emily Anne (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Inorganic chemistry research in the modern era predominantly revolves around the captivating realm of coordination chemistry. A fundamental component of this field is the study of transition metals, which are characterized by their incomplete d or f subshells in their elemental or ionic states (Huheey et al., 1993). This introduction sets the stage for exploring the multifaceted aspects of transition metals in coordination chemistry research. Transition metals, positioned within the same period of the periodic table, exhibit gradual changes in their atomic and ionic radii as well as ionization potentials from one element to the next. This subtle progression creates a fascinating landscape for investigation and has significant implications for their chemical behavior. Furthermore, transition metals are known for their ability to exist in multiple valence states, a feature that greatly influences the formation of complex compounds. This intricate chemistry leads to the creation of a plethora of colorful and paramagnetic coordination complexes, further highlighting the unique attributes of these elements. Transition metal complexes are not just of academic interest; they find extensive practical applications in today’s world of applied chemistry. Many transition metal complexes serve as highly effective catalysts, catalyzing a variety of chemical reactions crucial for numerous industrial processes. This critical role in catalysis underscores the importance of understanding the chemistry and behavior of transition metals in coordination compounds. This paper explores the captivating world of transition metals in coordination chemistry, shedding light on their atomic characteristics, multiple valence states, and the remarkable complexity of their coordination complexes